2019
DOI: 10.3390/molecules24162924
|View full text |Cite
|
Sign up to set email alerts
|

ANOVA Design for the Optimization of TiO2 Coating on Polyether Sulfone Membranes

Abstract: There have been developments in the optimization of polyether sulfone (PES) membranes, to provide antifouling and mechanically stable surfaces which are vital to water purification applications. There is a variety of approaches to prepare nanocomposite PES membranes. However, an optimized condition for making such membranes is in high demand. Using experimental design and statistical analysis (one-half fractional factorial design), this study investigates the effect of different parameters featured in the fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Among the numerous methods that can be used for metal ion removal from aqueous effluents (such as chemical precipitation, membrane separation, ions exchange, adsorption, etc.) [ 5 , 6 , 7 , 8 , 9 ], biosorption has several unique advantages, which are very important from a practical point of view. Thus, the possibility of using a large number of solid materials of biologic origin, which are cheap and readily available in most regions of the world, as well as having flexibility and adaptability to various experimental conditions [ 10 , 11 , 12 ], are just two advantages that highlight the importance of biosorption in treatment of aqueous effluents containing metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous methods that can be used for metal ion removal from aqueous effluents (such as chemical precipitation, membrane separation, ions exchange, adsorption, etc.) [ 5 , 6 , 7 , 8 , 9 ], biosorption has several unique advantages, which are very important from a practical point of view. Thus, the possibility of using a large number of solid materials of biologic origin, which are cheap and readily available in most regions of the world, as well as having flexibility and adaptability to various experimental conditions [ 10 , 11 , 12 ], are just two advantages that highlight the importance of biosorption in treatment of aqueous effluents containing metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the separation performance of membranes, it has been suggested that different organic or inorganic materials, such as fluorescent material (TPE) [ 8 ], metal nanoparticles [ 9 ], graphene oxide (GO) [ 10 ], carbon nanotubes (CNTs) [ 11 ], metal–organic frameworks (MOFs) [ 12 ], TiO 2 [ 13 , 14 ] and silica [ 15 , 16 ] are incorporated. Compared with other materials, silica is a common and low-cost functional filler for organic–inorganic hybrid membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane filtration, flocculation, biological treatments, photocatalytic oxidation, and adsorption [6][7][8][9][10] are some of the commonly used textile effluent treatment processes. On the other hand, the application of polymer materials in water treatment and selective sequestration has impressively developed in the last decades, with the production of novel materials and composites, post-polymerization modifications, introduction of functional groups, and development of supramolecular assemblies and nanomaterials [11][12][13][14][15][16]. However, these methods have their own limitations and efficiencies in terms of cost effectiveness.…”
Section: Introductionmentioning
confidence: 99%